Excitatory Actions of GABA in the Suprachiasmatic Nucleus - Choi, Hee Joo (Society for Neuroscience, 2008)
Neurons in the suprachiasmatic nucleus (SCN) are responsible for the generation of circadian oscillations, and understanding how these neurons communicate to form a functional circuit is a critical issue. The neurotransmitter GABA and its receptors are widely expressed in the SCN where they mediate cell-to-cell communication. Previous studies have raised the possibility that GABA can function as an excitatory transmitter in adult SCN neurons during the day, but this work is controversial. In the present study, we first tested the hypothesis that GABA can evoke excitatory responses during certain phases of the daily cycle by broadly sampling how SCN neurons respond to GABA using extracellular single-unit recording and gramicidin-perforated-patch recording techniques. We found that, although GABA inhibits most SCN neurons, some level of GABA-mediated excitation was present in both dorsal and ventral regions of the SCN, regardless of the time of day. These GABA-evoked excitatory responses were most common during the night in the dorsal SCN region. The Na(+)-K(+)-2Cl(−) cotransporter (NKCC) inhibitor, bumetanide, prevented these excitatory responses. In individual neurons, the application of bumetanide was sufficient to change GABA-evoked excitation to inhibition. Calcium-imaging experiments also indicated that GABA-elicited calcium transients in SCN cells are highly dependent on the NKCC isoform 1 (NKCC1). Finally, Western blot analysis indicated that NKCC1 expression in the dorsal SCN is higher in the night. Together, this work indicates that GABA can play an excitatory role in communication between adult SCN neurons and that this excitation is critically dependent on NKCC1.